Kuznetsov A. Yu. Verse adaptation for the successful vocal performans: translation aspects - Kuznetsov A. Yu. (Philological Treatises, 2020)
The article is devoted to the study of interaction of verbal and music semiotic systems and its influence on poetic translation. The process of the translation adaptation is analysed on the material of the translation of R. Burns‟ poem “O Wert Thou In The Cauld Blast”.